120 Minima timings of eclipsing binaries - Palafouta, S.; Gazeas, K.; Christopoulou, E.; Bakogianni, V.; Dervou, M.; Loukaidou, G. (2017)
We present 120 times of minima of 8 eclipsing binaries.
Keywords: CCD photometry